Perancangan Manajemen Proyek Sistem Informasi Akademik Dengan Critical Path Method Dan Program Evaluation And Review Technique - Turang, Daniel Alexander Octavianus; Zaini, Zaini (INTEK : Jurnal Informatika dan Teknologi Informasi, 2018)
Project management is an implementation of the majemen in a project to manage and achieve a certain result. Project management is required for to achieve the efficiency and effectiveness of an enterprise. Research on design of project management using the Cirital Path Method (CPM) and Program Evaluation and Review Technique (PERT). Project management can be used to estimate the acceleration of the project (crashing). Good project management is able to optimise time and cost, so it is able to reduce losses due to the delay of the project. The research results obtained the academic information system project scheduling with CPM and PERT obtained time for completion of the whole project that is 48 weeks and slack time 8 weeks with the success of the project of 72.57% and cost budgeted IDR 21,063,000. From the results of the calculation of the crashing, the project implementation of 48 weeks to 27 weeks. The total cost of the activity on the crashing of IDR 24,164,000. If the calculated costs based on the magnitude of the difference in the cost of crashing and normal, then there is an increased cost that is amounting to IDR 3,101,000.